THE PECULIARITIES OF APPLICATION OF THE FUNDAMENTAL PRINCIPLES OF THE INTERNATIONAL LABOUR ORGANIZATION IN THE MECHANISM OF MANAGEMENT OF SOCIO-LABOUR RELATIONS OF THE ENTERPRISES OF UKRAINIAN AVIATION TRANSPORT - Yarovyi, I. M. (Science and Transport Progress, 2007)
The features of regulation of the social - labour relations in civil aircraft of Ukraine are considered. The role and meaning of principles of management of the social - labour relations, their place in the mechanism of management is proved. The formulation of algorithm of acceptance of the decision about expediency of application of the international experience in personnel selection of the airenterprises of Ukraine is carried out. The critical analysis of fundamental principles of management is carried out which are recognized by the International organization of work and can be used by a manual of the airenterprises of Ukraine for improvement of the relations in social-labour sphere.